The Influence of Multimorbidity on Leading Causes of Death in Older Adults With Cognitive Impairment. (July 2019) - Schiltz, Nicholas K.; Warner, David F.; Sun, Jiayang; Smyth, Kathleen A.; Gravenstein, Stefan; Stange, Kurt C.; Koroukian, Siran M.
Objective: The aim of this study is to evaluate the relationship of leading causes of death with gradients of cognitive impairment and multimorbidity.Method: This is a population-based study using data from the linked 1992-2010 Health and Retirement Study and National Death Index ( n = 9, 691). Multimorbidity is defined as a combination of chronic conditions, functional limitations, and geriatric syndromes. Regression trees and Random Forest identified which combinations of multimorbidity associated with causes of death.Results: Multimorbidity is common in the study population. Heart disease is the leading cause in all groups, but with a larger percentage of deaths in the mild and moderate/severe cognitively impaired groups than among the noncognitively impaired. The different "paths" down the regression trees show that the distribution of causes of death changes with different combinations of multimorbidity.Discussion: Understanding the considerable heterogeneity in chronic conditions, functional limitations, geriatric syndromes, and causes of death among people with cognitive impairment can target care management and resource allocation.